EVALUATION STUDY FOR SOME AVAILABLE SOIL POTASSIUM EXTRACTION METHODS AND ITS RELATIONSHIP WITH ABSORBED POTASSIUM BY BARLEY CROP - & bdulrasol, Asaad (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
Two pots experiments were conducted one of silty clay loam texture and the other in loamy sand texture by planting barley crop variety “Samir” to evaluate extraction efficiency of seven chemical extractants via the correlation with the potassium taken up by barley crop. Four of these extractants were: BaCl2, CaCl2, MgCl2 and NaC l; the remaining three were: CH3COONH4, NH4HCO3, NH4HCO3 + DTPA. The study was performed by the application of four levels of potassium sulfate fertilizer (41.5 % K): 0, 50, 100, and 150 kg K ha-1 in four replicates using RCBD design . At the end of the agricultural season, soil available potassium was extracted using these extractants. Plant samples (straw+ cereal) were digested to test K taken up by plants. Results indicated: that available potassium increased potassium uptake in both soils with increasing of amount potassium fertilizer applied. Results of the study also showed differences in extractants efficiency in both soils textures through correlation between K extracted and absorbed. All chlorides extractants except Barium chloride have shown superiority on ammoniac extractants in fine texture soil while the ammoniac extractants except CH3COONH4 showed superiorityon chloride extractants in coarse texture soil.The efficiency of the extractants in soils were as follows: in coarse soils NH4HCO3+DTPA > CaCl2 > NH4HCO3 >MgCl2, in fine soils NaCl > MgCl2 = CaCl2> CH3COONH4 This study concluded that calcium chloride extractants had good efficiency in both soils, followed by magnesium chloride extractant.